2007
DOI: 10.1507/endocrj.k06-176
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Activatable Fibrinolysis Inhibitor Antigen Levels Are Inversely Correlated with Plasminogen Activator Inhibitor-1 Antigen Levels in Hyperthyroid Patients

Abstract: Abstract. Both increased and decreased fibrinolytic activity have been reported in patients with hyperthyroidism. Elevated levels of plasma plasminogen activator inhibitor-1 (PAI-1) antigen have been found in hyperthyroid patients. Thrombin activatable fibrinolysis inhibitor (TAFI) is a novel plasma protein, which inhibits fibrinolysis through removal of C-terminal lysines from partially degraded fibrin. Previously, we showed that plasma TAFI antigen levels were increased in patients with overt and subclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
3
22
2
Order By: Relevance
“…LT4 suppression treatment resulted in a non-significant increase in PAI-1 antigen levels. In accordance with our previous study [12] , TAFI antigen levels were found to be decreased in patients with endogenous hyperthyroidism. Endogenous hyperthyroid patients had significantly increased PAI-1 antigen levels when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…LT4 suppression treatment resulted in a non-significant increase in PAI-1 antigen levels. In accordance with our previous study [12] , TAFI antigen levels were found to be decreased in patients with endogenous hyperthyroidism. Endogenous hyperthyroid patients had significantly increased PAI-1 antigen levels when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that LT4 replacement treatment effectively reduced increased TAFI antigen levels in hypothyroidism. In a more recent study, we were able to detect reduced TAFI antigen levels in hyperthyroid patients [12] . In the present study, however, we failed to show any significant decrease in TAFI antigen levels after LT4 suppression treatment for benign thyroid nodules.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Several in vivo studies on the effect of overt thyroid dysfunction on blood coagulation and fibrinolytic factors suggest that a procoagulant state might be associated with hyperthyroidism, but no reliable evidence has been provided so far on the potential biological mechanism because neither temporary nor permanent thromboembolic risk factors were consistently identified throughout the studies [7][8][9][10]. Compared with control subjects, increased values of von Willebrand factor (VWF), factor VIII factor IX, antithrombin, plaminogen activator inhibitor 1 (PAI-1) and decreased values of factor X, tissue plasminogen activator (t-PA) and TAFI were observed in patients with hyperthyroidism [13][14][15]. Significantly increased serum thrombomodulin were found by Morikawa et al in patients with Graves' disease [16].…”
Section: Discussionmentioning
confidence: 99%